2006
DOI: 10.1103/physrevb.74.245414
|View full text |Cite
|
Sign up to set email alerts
|

Stability and symmetry breaking in metal nanowires: The nanoscale free-electron model

Abstract: A general linear stability analysis of simple metal nanowires is presented using a continuum approach which correctly accounts for material-specific surface properties and electronic quantum-size effects. The competition between surface tension and electron-shell effects leads to a complex landscape of stable structures as a function of diameter, cross section, and temperature. By considering arbitrary symmetry-breaking deformations, it is shown that the cylinder is the only generically stable structure. Never… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(53 citation statements)
references
References 44 publications
4
49
0
Order By: Relevance
“…These observations form the basis for the nanoscale free-electron model (NFEM [11,29,41]) which considers electrons in the wire to be free (other than being confined within the wire) and non-interacting. The former works best for s-shell metals, such as alkali and to some extent noble metals like gold, but has also been shown to perform well for metals whose Fermi surface in the extended zone scheme is nearly spherical, such as Al [14].…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations form the basis for the nanoscale free-electron model (NFEM [11,29,41]) which considers electrons in the wire to be free (other than being confined within the wire) and non-interacting. The former works best for s-shell metals, such as alkali and to some extent noble metals like gold, but has also been shown to perform well for metals whose Fermi surface in the extended zone scheme is nearly spherical, such as Al [14].…”
Section: The Modelmentioning
confidence: 99%
“…The theory, however, is limited to wires with a cylindrical symmetry. Urban et al [9,11], using a stability analysis of metal nanowires subject to non-axisymmetric perturbations, showed that, at certain mean radii and aspect ratios, Jahn-Teller deformations breaking cylindrical symmetry can be energetically favorable, leading to an additional class of stable nanowires with non-axisymmetric cross sections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus particularly suitable as a model of metal nanowires, and successfully describes many of their equilibrium [2,11,12,15,18,19] and dynamical [3,4,9,16,20] properties in simple physical terms.…”
Section: The Nanoscale Free-electron Modelmentioning
confidence: 99%
“…It has been shown, using the NFEM [4,12], that the quantum confinement of electrons in the cross-section of the wire provide electron-shell effects-similar to those well-known in cluster physics [13]-that compete with surface effects, and stabilize cylindrical wires for a finite range around magic radii [11,12], as well as a number of number of wires with broken axial symmetry [14,15].…”
mentioning
confidence: 91%